THE INFLUENCE OF THE SCHOOL ENVIRONMENT ON TEENAGE DELINQUENCY IN STUDENTS OF SMP N 1 BANJARMANGU - IHZA FAUZI, PRAYOGA (Jurnal Psikoedukasia, 2025)
The Influence of the School Environment on Juvenile Delinquency in Students at SMP Negeri 1 Banjarmangu. Guidance and counseling. Faculty of Education. PGRI University Semarang. 2024. The background to this research is that there is still juvenile delinquency among Banjarmangu State Middle School students. The aim of this research is to determine the influence of the school environment on juvenile delinquency among students at SMP Negeri 1 Banjarmangu. The population in this study was class VII students at SMP N Banjarmangu. This type of research is correlation research. The sample in the research consisted of 30 students. Retrieval of data using a scale. The data analysis technique uses rxy product moment. The research results showed that there was a positive and significant influence between the school environment and juvenile delinquency in class VII SMP N 1 Mangunharjo. This result is proven by the product moment correlation test, obtaining a calculated correlation value of 0.3768. Meanwhile, the rtable for the sample size is 30 with a significance level of 5%, which is 0.361. Therefore, rcount ˃ rtable. So it can be said that "there is an influence between the school environment and juvenile delinquency in class VII SMP N 1 Banjarmangu". Suggestions that can be conveyed should be that as a guidance and counseling teacher, in implementing student delinquency prevention, there needs to be a different method or technique for dealing with it.